Early treatment with Resolvin E1 facilitates myocardial recovery from ischaemia in mice. (22nd October 2017) - Liu, Guizhu; Liu, Qian; Shen, Yujun; Kong, Deping; Gong, Yanjun; Tao, Bo; Chen, Guilin; Guo, Shumin; Li, Juanjuan; Zuo, Shengkai; Yu, Yu; Yin, Huiyong; et al.
Abstract : Background and Purpose: An appropriate inflammatory response is necessary for cardiac healing after acute myocardial infarction (MI). Resolvin E1 (RvE1) is an anti‐inflammatory and pro‐resolution lipid mediator derived from eicosapentaenoic acid. Here we have investigated the effects of RvE1 on the recovery of cardiac function after MI in mice. Experimental Approach: Acute MI was induced by surgical ligation of the left anterior descending artery in male C57BL/6 mice. RvE1 (5 ng·g −1 ·day −1 ; i.p.) was given to mice at different times following MI. Cardiac function was monitored by transthoracic echocardiography at days 3, 7 and 14 after MI. Effects of RvE1 on the migration of subpopulations of monocytes/macrophages (Mos/Mps, Ly6C hi and Ly6C low ) were examined by flow cytometry and transwell assay. Key Results: RvE1 administration from days 1 to 7 post‐MI improved cardiac function, whereas treatment from days 7 to 14 markedly inhibited recovery of cardiac function. Early treatment with RvE1 post‐MI suppressed the infiltration of dominant Ly6C hi Mos/Mps and secretion of pro‐inflammatory cytokines in injured hearts, which protected cardiomyocytes against apoptosis in the peri‐infarct zones. Contrastingly, treatment with RvE1 1 week after MI decreased infiltration of Ly6C low Mos/Mps and expression of pro‐angiogenic factors in cardiac tissue, consequently reducing neovascularization in the peri‐infarct zones. Additionally, RvE1 inhibited Mp migration by activating ChemR23 receptors. Conclusion and Implications: Treatment with RvE1 during the initial 7 days after MI facilitated cardiac healing by suppressing pro‐inflammatory cytokine secretion, indicating that RvE1 may serve as an early therapeutic agent for acute MI. Linked Articles: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc